Longitudinal magnetic resonance imaging detects onset and progression of chronic rhinosinusitis from infancy to school age in cystic fibrosis - Wucherpfennig, Lena; Wünnemann, Felix; Eichinger, Monika; Schmitt, Niclas; Seitz, Angelika; Baumann, Ingo; Stahl, Mirjam; Gräber, Simon Y.; Chung, Jaehi; Schenk, Jens-Peter; Alrajab, Abdulsattar; Kauczor, Hans-Ulrich; et al. (Annals of the American Thoracic Society, 2023)
Rationale: Chronic rhinosinusitis (CRS) contributes to morbidity in patients with cystic fibrosis (CF). However, longitudinal data on CRS onset and progression is lacking. - - Objectives: To longitudinally evaluate CRS in CF from infancy to school age with paranasal sinus magnetic resonance imaging (MRI). - - Methods: A total of 64 children with CF (mean age at baseline, 1.1 ± 1.6 yr; range, 0-5 yr) underwent a mean of 5.8 ± 2.2 (range, 3-11 yr) subsequent annual MRI examinations. Additional 24 children (9.2 ± 4.4 yr; range, 3-17 yr) homozygous for the F508del mutation underwent MRI before and at least 2 months after starting lumacaftor/ivacaftor. MRI was assessed using the previously evaluated CRS-MRI score. - - Results: In infancy, 65-87% of paranasal sinuses were opacified, and mucosal swelling was the dominant abnormality (58-97%). At preschool age (1-5 yr), 79-94% of sinuses were opacified (P < 0.05 vs. infancy), and mucosal swelling was the most dominant abnormality (79-94%; P < 0.05). At school age (at least 6 yr), almost all sinuses were opacified (71-99%; P < 0.001-0.357 vs. preschool age), and mucopyoceles were the dominant abnormality in maxillary and frontal sinuses (53-56%; P < 0.05-0.808). The CRS-MRI sum score increased from 22.4 ± 9.6 in infancy to 34.2 ± 9.6 in preschool age (P < 0.001) and was 34.0 ± 5.7 in school age (P = 0.052). In children under lumacaftor/ivacaftor therapy, the CRS-MRI sum score (−0.5 ± 3.3; P < 0.05) and maxillary sinus subscore (−0.5 ± 1.5; P < 0.05) improved. - - Conclusions: Longitudinal paranasal sinus MRI detects an early onset and progression of the severity of CRS from infancy to school age, and response to lumacaftor/ivacaftor therapy in children with CF. Our data support its role in the comprehensive noninvasive monitoring of CRS in children with CF. - - Clinical trial registered with www.clinicaltrials.gov (NCT 02270476).
Gesehen am 20.06.2023